2017
DOI: 10.1590/0034-7167-2016-0143
|View full text |Cite
|
Sign up to set email alerts
|

Communicating bad news: an integrative review of the nursing literature

Abstract: Objectives: describe how the process of breaking bad news is established and identify how nurses approach the task of giving bad news. Method: integrative review of the literature for articles in Portuguese and English published between 1993-2014, in the databases: Bireme, PubMed, Scopus, Web of Science, CINAHL and Embase. Nine articles were included using the selection fl ow chart. A digital form was completed for each article according to the Consolidated Criteria for Reporting Qualitative Research checklist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
38

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 14 publications
1
25
0
38
Order By: Relevance
“…11,13 While the opposite brings the nurse closer to the care of the patient and their family, making the process of dying more intimate and probably less vicarious. [14][15] Regarding the process of communicating with the patient's family regarding the death and dying process, it was pointed out that some family members questioned nurses and nursing technicians about the possibility of their beloved ones getting better, but they did not usually talk openly about the process of death and dying.…”
Section: /14mentioning
confidence: 99%
See 4 more Smart Citations
“…11,13 While the opposite brings the nurse closer to the care of the patient and their family, making the process of dying more intimate and probably less vicarious. [14][15] Regarding the process of communicating with the patient's family regarding the death and dying process, it was pointed out that some family members questioned nurses and nursing technicians about the possibility of their beloved ones getting better, but they did not usually talk openly about the process of death and dying.…”
Section: /14mentioning
confidence: 99%
“…It was identified that the nursing communication with the relatives of the patients was significantly crossed by the doctor's communication, corroborating other studies. [15][16] Regarding this (inter)action, insensitivity and lack of clarity were listed as communication failures of some attending doctors towards family members. Such behaviors made it difficult for the family members to experience the death and dying process, as well as the health professionals' performance.…”
Section: /14mentioning
confidence: 99%
See 3 more Smart Citations